2018
DOI: 10.1103/physreva.98.063814
|View full text |Cite
|
Sign up to set email alerts
|

Creation, storage, and retrieval of an optomechanical cat state

Abstract: We analyze a method for the creation, storage and retrieval of optomechanical Schrödinger cat states, in which there is a quantum superposition of two distinct macroscopic states of a mechanical oscillator. In the quantum memory protocol, an optical cat state is first prepared in an optical cavity, then transferred to the mechanical mode, where it is stored and later retrieved using control fields. We carry out numerical simulations for the quantum memory protocol for optomechanical cat states using the positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 100 publications
(177 reference statements)
0
27
0
Order By: Relevance
“…A positive-valued Wigner function gives δ = 0 while δ is nonzero in the presence of any negative values in a Wigner function. The Wigner functions W + and W − for the even cat-state and odd cat-state respectively are given by [89] W ± (α, α * ) = 2 π N 2 ± {exp [−2 (α * − α * 0 ) (α − α 0 )] +exp [−2 (α * + α * 0 ) (α + α 0 )]…”
Section: A Wigner Function and Its Negativitymentioning
confidence: 99%
“…A positive-valued Wigner function gives δ = 0 while δ is nonzero in the presence of any negative values in a Wigner function. The Wigner functions W + and W − for the even cat-state and odd cat-state respectively are given by [89] W ± (α, α * ) = 2 π N 2 ± {exp [−2 (α * − α * 0 ) (α − α 0 )] +exp [−2 (α * + α * 0 ) (α + α 0 )]…”
Section: A Wigner Function and Its Negativitymentioning
confidence: 99%
“…We consider a system which consists of two coupled cavities [29] with modulation time-dependent jumping rate. [27,28,30] The two mode cavities share a common movable mirror which couples to the first and second cavity with a linear and quadratical coupling [46,47] respectively.…”
Section: Model and The Analytic Solutionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26] Most recently, generating cat state of mechanical oscillator has caught people's attention. [27][28][29][30] Liao proposed a scheme to create macroscopically mechanical superposition states in a twomode optomechanical system by introducing modulated sinusoidal photon hopping between the two cavity modes. [27,28] Teh [29] showed that an optical cat state could be transferred to the DOI: 10.1002/andp.201900196 mechanical mode, where it was stored and later retrieved using control fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we propose a scheme for preparation of a mechanical catlike state in quantum optomechanics that does not rely on nonlinear coupling [38,40,41] or on external generation and transfer of the nonclassical state [44,57]. An established technique for preparation of catlike states is subtraction of one or several quanta from a squeezed vacuum state [58,59].…”
Section: Introductionmentioning
confidence: 99%